Physicochemical approach to freshwater microalgae harvesting with magnetic particles - Prochazkova, Gita; Podolova, Nikola; Safarik, Ivo; Zachleder, Vilem; Branyik, Tomas (Colloids and surfaces. B, Biointerfaces, 2013)
Magnetic harvesting of microalgal biomass provides an attractive alternative to conventional methods. The approach to this issue has so far been pragmatic, focused mainly on finding cheap magnetic agents in combination with harvestable microalgae species. The aim of this work was to study experimentally and theoretically the mechanisms leading to cell-magnetic agent attachment/detachment using real experiments and predictions made by colloidal adhesion (XDLVO) model. Two types of well defined magnetic beads (MBs) carrying ion exchange functional groups (DEAE - diethylaminoethyl and PEI - polyethylenimine) were studied in connection with microalgae (Chlorella vulgaris). Optimal harvesting efficiencies (>90%) were found for DEAE and PEI MBs, while efficient detachment was achieved only for DEAE MBs (>90%). These findings were in accordance with the predictions by XDLVO model. Simultaneously there was found a discrepancy between the XDLVO prediction and the poor detachment of PEI MBs from microalgal surface. This can be ascribed to an additional interaction (probably covalent bonds) between PEI and algal surface, which the XDLVO model is unable to capture given by its non-covalent nature.
Keywords: mikrořasy; Chlorella vulgaris; Ethanolamines; povrchové vlastnosti; XDLVO theory; průmyslová mikrobiologie; iontová výměna; ethanolaminy; Models, Biological; Cell Adhesion; magnetické jevy; biomasa; sladká voda; Surface interactions; Magnetite Nanoparticles; Ion Exchange; Fresh Water; Polyethyleneimine; biologické modely; Colloids; magnetické nanočástice; Magnetic beads; buněčná adheze; Magnetic Phenomena; Biomass; Microalgae; Industrial Microbiology; Cell adhesion; polyethylenimin; Surface Properties; koloidy